Love Liza - Hanley, Chris (Film producer); Sulichin, Fernando; Louiso, Todd (Academic Video Online, 2002)
Winner of the Waldo Salt Screenwriting award at the 2002 Sundance Film Festival, Love Liza a tour de force performance by Philip Seymour Hoffman, one of this country's most original actors. Set somewhere in Middle America, Wilson Joel (Philip Seymour Hoffman), a successful website designer, suddenly sees his world stop with the untimely death of his young wife Liza. Trying to make sense of everything that has just happened, Wilson turns to his mother-in-law (Kathy Bates) for support. Their relationship intensifies when Wilson refuses to open a letter Liza left behind for fear it will shatter his ideal of the perfect life they shared. As Wilson attempts to rebuild his life, with unopened letter in tow, eccentric behavior begins to surface taking him on an odyssey of self-pity, self-realization and a curious fascination with remote-control model enthusiasts. Through this temporary comfort, he begins dealing with his grief. Love Liza is a beautifully drawn portrait of a survivor who invokes humor, humility and whatever it takes to find the possibilities for a successful resolution.